Changes in the diagnosis and treatment of patients with low grade lymphoma in Germany: years 2006–2009. Issue 3 (March 2015) - Schmidt, Christian; Fingerle-Rowson, Guenter; Boehme, Angelika; Brendel, Kurt; Fischer, Richard; Gonnermann, Michael; Höhler, Thomas; Kegel, Thomas; Kellermann, Lenka; Nusch, Arndt; Pönisch, Wolfram; Wendtner, Clemens; et al.
Abstract: Today's treatment options for indolent lymphoma and chronic lymphocytic leukemia (CLL) range from watch & wait, immunochemotherapy up to allogeneic transplantation. We describe changes in the diagnosis and treatment of indolent lymphoma and CLL in Germany between 2006 and 2009. Two nation-wide surveys in the fourth quarter of 2006 and 2009 included patients with indolent lymphoma and CLL. Data from 576 patients from 46 centers in Q4/2006 were compared with data from 521 patients from 57 centers in Q4/2009. The subpopulation of patients ≥ 70 years of age and the number of patients with comorbidities increased from 39% to 55% and 47% to 55%, respectively. Both in indolent lymphoma and CLL, Rituximab and R-based immunochemotherapy (50.6% vs. 64.4%) as well as bendamustine (4.8 % vs. 24%) were much more frequently applied. In contrast, high dose chemotherapy consolidation was almost abandoned in first line treatment. Supportive care is given more frequently, with exception of erythropoietin and immunoglobulins. Our national survey confirmed that scientific results were rapidly transferred into clinical care of indolent lymphoma.